GAMBAR CADAS Dl KABUPATEN BERAU: INFORMASI AWAL - Bambang Sugiyanto (Naditira Widya, 2007)
In addition to some rock arts sites found in Kalimantan Barat, there are some other rock art sites found recently in several caves, Kalimantan Timur such as in Jufri cave, Te 'et cave, Tewet cave, Tengkorak cave, lias Kenceng cave, Ham cave, Tembus cave, Tebok cave, and Tamrin cave. This article describes several varieties of rock art motif found in both regions and also some administrative problems accidentally faced by my team before archaeological survey was carried out in Kutai Timur District. The purpose is to share this experience with other research teams to prevent uncomfortable experience in the future.